Basics of Photovoltaic Panels and an Overview of the Use of Solar Energy in the World - Sabzalian , M (Elsevier, 2024)
This chapter includes an overview of the history of using the sun as an energy source, introduction of photovoltaic systems, trade and business around solar energy now, the cost of electricity produced with photovoltaic technology, and advantages and disadvantages of using solar energy. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.
Keywords: advantages; basics; disadvantages; photovoltaic; Review; solar energy